The Development of Thermodynamics Law Experiment Media Based on IoT: Laboratory Activities Through Science Problem Solving for Gifted Young Scientists - Yeni Rima Liana; S Linuwih; S Sulhadi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
In this research, thermodynamics law experiment media based on IoT (Internet of Things) was developed and tested. The purpose was to assess the effectiveness of the IoT-based thermodynamic law experiment media through a problem-based learning approach and laboratory activities using science problem solving for talented young scientists. This research was conducted at SMA 2 Batang. This study using the ADDIE approach model. The development steps are: (1) analyzing curriculum requirements and demands in 2013, (2) designing and manufacturing, (3) developing media, (4) limited through small-scale tests, expert testing, tested on professional physics teachers and student grade XI sciences, (5) evaluated to get feedback in the form of comments and suggestions. This media is equipped with an LCD display to read of temperature, electric current, and electrical voltage in real-time, which is integrated with the Thingspeak application on every student’s android phone. This media is easily assembled, based on digital, equipped with manuals and student worksheets. The validation results from the media experts 90.20% (Very Good), the results of the validation from the material experts 91.50% (Very Good), and the results of the physics teacher’s responses covering all aspects of the material and multimedia 93.00% (Very Good). The results of the validation show that thermodynamics law experiment media based on IoT is appropriate to be used as a media for learning activities in the thermodynamics law material laboratory.